Penguatan Nilai Moderasi Beragama Melalui Kegiatan Bermain Edukatif Pada Anak Usia Dini - Annisa Wahyuni (Jurnal Pengabdian Masyarakat, 2026)
Strengthening religious moderation in early childhood is a strategic effort to foster tolerant and inclusive character values within multicultural societies. The increasing prevalence of intolerance and the influence of digital media on children’s behavioral development highlight the urgency of introducing religious moderation values from an early age through approaches that align with children’s developmental characteristics. This community service program aimed to strengthen religious moderation values among early childhood learners through educational play activities that are interactive and developmentally appropriate. The program employed a qualitative descriptive approach using the Participatory Action Research (PAR) method. The implementation stages included problem identification, program planning, educational play activities, observation, and evaluation. Data were collected through observation, interviews, and documentation techniques. The educational activities consisted of storytelling, role-playing, collaborative games, and creative art activities integrating values of tolerance, cooperation, empathy, and respect for diversity. The findings demonstrated significant positive changes in children’s social behavior, including improved cooperation, sharing attitudes, respect for peers, and harmonious interaction regardless of social or religious backgrounds. Furthermore, teachers and parents showed increased understanding of the implementation of religious moderation values in both learning activities and daily life practices. Therefore, educational play activities proved effective in strengthening religious moderation values in early childhood while promoting an inclusive and harmonious learning environment.